Efficacy of Human-Recombinant Epidermal Growth Factor Combined with Povidone-Iodine for Pressure Ulcers and Its Influence on Inflammatory Cytokines - Zunjiang Zhao; Dalun Lv; Baode Zhang; Liu Yong; Rongtao Zhang; Xiukun Wang (Mediators of Inflammation)
Purpose. To determine the clinical efficacy of recombinant human epidermal growth factor (rh-EGF) combined with povidone-iodine (PVI) on patients with pressure ulcers (PUs). Methods. One hundred and five PU patients treated between January 2018 and January 2021 were enrolled and retrospectively analyzed. Of them, 50 patients who received conventional treatment were assigned to the control group (Con group), while 55 patients treated with rh-EGF combined with PVI were assigned to the observation group (Obs group). The two groups were compared in clinical efficacy, PU alleviation (total area reduction rate, total depth reduction rate, and total volume reduction rate), healing time, pain degree (Visual Analog Scale [VAS] score), inflammatory indexes (interleukin-8 [IL-8], tumor necrosis factor-α [TNF-α], and hypersensitive C reactive protein [hs-CRP]), and hydroxyproline content in the wound. Results. The Obs group yielded a higher total effective rate than the Con group (P<0.05). The Obs group also experienced statistically shorter healing time and milder pain, with better PU alleviation and lower levels of inflammation indexes compared with the Con group (all P<0.05). In addition, a higher hydroxyproline content in the wound was found in the Obs group. Conclusions. All in all, rh-EGF combined with PVI has a definite curative effect on patients with PUs. It can promote PU alleviation and hydroxyproline secretion in the wound and inhibit pain and inflammatory reactions, which is worthy of clinical promotion.